Complications and management of long-term central venous access catheters and ports - (:unkn) unknown (Wichtig Editore s.r.l., 2004)
Purpose: Although prolonged venous access devices (PVADs) are used in case prolonged intravenous therapy is required, implantation and use of these devices is associated with complications. The purpose of this study was to evaluate perioperative and long-term complications associated with PVADs and the management of these complications. Methods: A retrospective review was undertaken of 225 PVADs implanted in 217 patients from February 1993 to June 2004. This included 144 single-lumen port infusion systems, 49 single-lumen Hickman® catheters and 32 double-lumen Groshong® catheters. The PVADs were inserted using either the percutaneous Seldinger method (n=183) or cutdown access to the subclavian vein (n=42). Indications for placement were as follows: chemotherapy in 66.2% of patients, drug-infusion treatment in 31.6% of patients and total parenteral nutrition in 2.2% of patients. Results: Perioperative complications occurred in 13 patients (5.7%): catheter malposition in seven patients (3.1%), pneumothorax in three patients (1.3%), hemorrhage in two patients (0.9%) and catheter embolization in one patient (0.4%). Long-term complications appeared in 15 patients (6.6%): infection in five patients (2.2%), thrombosis in three patients (1.3%), extravasation in three patients (1.3%), and catheter fracture in four patients (1.8%). The fractured fragments were removed by the Amplatz® snare device. In 10 patients (4.4%) only were PVADs removed prior to completion of the intended therapy. Indications for removal were catheter infection in five patients (2.2%) and catheter fracture in five patients (2.2%). Conclusions: PVAD implantation is associated with some risk of serious perioperative and long-term complications. Care of the catheter and the patient should be maintained with the proper and immediate evaluation of the perioperative and long-term complications. © Wichtig Editore, 2004.
Keywords: Complications; Management; Venous access devices